2019
DOI: 10.1007/s00125-019-4824-2
|View full text |Cite
|
Sign up to set email alerts
|

DOC2B promotes insulin sensitivity in mice via a novel KLC1-dependent mechanism in skeletal muscle

Abstract: Aims/hypothesis Skeletal muscle accounts for >80% of insulin-stimulated glucose uptake; dysfunction of this process underlies insulin resistance and type 2 diabetes. Insulin sensitivity is impaired in mice deficient in the double C2 domain β (DOC2B) protein, while whole-body overexpression of DOC2B enhances insulin sensitivity. Whether insulin sensitivity in the skeletal muscle is affected directly by DOC2B or is secondary to an effect on other tissues is unknown; the underlying molecular mechanisms also remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 58 publications
1
35
0
Order By: Relevance
“…In neurons, Syt1 and Doc2b each contribute to synaptic vesicle secretion but exhibit very distinct kinetics: Syt1 triggers fast synchronous neurotransmission evoked by action potentials and the subsequent opening of voltage-gated Ca 2þ channels (41), whereas Doc2b contributes to the socalled spontaneous release events that occur in the absence of action potentials (34). In addition, Doc2b is also implicated in the secretion of chromaffin granules (37,42) and insulin (43) and the externalization of glucose transporters (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…In neurons, Syt1 and Doc2b each contribute to synaptic vesicle secretion but exhibit very distinct kinetics: Syt1 triggers fast synchronous neurotransmission evoked by action potentials and the subsequent opening of voltage-gated Ca 2þ channels (41), whereas Doc2b contributes to the socalled spontaneous release events that occur in the absence of action potentials (34). In addition, Doc2b is also implicated in the secretion of chromaffin granules (37,42) and insulin (43) and the externalization of glucose transporters (44,45).…”
Section: Introductionmentioning
confidence: 99%
“…Full-size DOI: 10.7717/peerj.11420/fig- 5 Qu, Chu & Wang (2017) demonstrated that miR-195-5p suppresses osteosarcoma cell proliferation and invasion by suppressing naked cuticle homolog 1. Zhang et al (2019) discovered that DOC2B promoted insulin sensitivity in mice via a novel KLC1-dependent mechanism in skeletal muscle. Importantly, we found that circRNA hsa_circ_0042409 and KLC1 mRNA were significantly increased while hsa-miR-195-5p was significantly decreased in male osteoporosis patients by whole transcriptome sequencing and further validated by qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, both STX4 and DOC2b is known to associate with microtubule-associated Tctex-1 type proteins, reinforcing the regulatory contribution of both of these exocytosis proteins in cytoskeletal remodeling [ 84 , 91 , 92 ]. Recently, DOC2b was shown to undergo tyrosine-phosphorylation at tyrosine 301, within its functionally indispensable C2B domain following insulin stimulation in the skeletal muscle, resulting in its association with microtubule protein kinesin light chain 1 (KLC1) [ 93 ]. KLC1 is a cytoskeletal motor protein with a proposed role in protein/vesicle translocation.…”
Section: Exocytosis Proteins and β-Cell Functionmentioning
confidence: 99%
“…KLC1 is a cytoskeletal motor protein with a proposed role in protein/vesicle translocation. The association of DOC2b-KLC1 is critical for its stimulatory role in glucose uptake in the skeletal muscle [ 93 ]. However, the precise contribution of DOC2b in cytoskeletal remodeling in the β-cell during insulin exocytosis is not known and calls for future investigation ( Figure 4 ).…”
Section: Exocytosis Proteins and β-Cell Functionmentioning
confidence: 99%
See 1 more Smart Citation